Joint Source and Relay Optimization for Parallel MIMO Relays Using MMSE-DFE Receiver - Toding, Apriana; Khandaker, Muhammad; Rong, Yue (IEEE, 2010)
In this paper, we study the optimal structure of the source precoding matrix and the relay amplifying matrices for multiple-input multiple-output (MIMO) relay communication systems with parallel relay nodes. In particular, a nonlinear decision feedback equalizer (DFE) is used at the destination node, and the minimal mean-squared error (MMSE) criterion is used to detect the transmitted signal at each stream. We show that the optimal source precoding matrix and the optimal relay amplifying matrices have a beamforming structure. Using such optimal source and relay matrices and the MMSE-DFE receiver, a joint source and relay power loading algorithm is developed to minimize the MSE of the signal waveform estimation. Compared with existing algorithms for parallel MIMO relay networks, theproposed source and relay design together with the MMSE-DFE receiver has a significant improvement in the system bit-errorrate performance.